Efikasi Diri, Sistem Imbalan, dan Berbagi Pengetahuan: Meta-analisis - Avin Fadilla Helmi; Yessi Elita (Buletin Psikologi, 2013)
Sharing of knowledge constitutes the basic concept of knowledge management and important aspect of knowledge management system because knowledge is viewed as the most valuable resource. Therefore, it is necessary to analyze any factor that influences sharing of knowledge. According to the research map made by Helmi (2008), sharing of knowledge is influenced by individual’s characteristics, which is self-efficacy, and reward system at the level of organization. The results of any existing researches on both seem to be less consistent. The purpose of this research is to study the results of researches having been done by researchers in the field of organization, finding out whether self-efficacy and reward system are consistently related to each other. They will be tested using meta-analysis method. Meta-analysis study results in self-efficacy and reward system contributes to sharing of knowledge.